Iqbal’s Allahabad Address and Its Impact on Muslim Political Struggle in Indian Sub-Continent - Shamshad, Muhammad; Usman, Asif (Al-Amīr Research Journal for Islamic Studies, 2023)
An independent state ensures the protection of the religious, social, political, economic, and cultural identities of its nationals. Such a state had become a dream of the Indian Muslims who could not evolve the mentioned identities with Hindus even after spending many centuries together. The absence of religious compatibility, social harmony, political similarity, economic equality, and cultural conciliation never allowed them to address the Indian cause of liberty from the British in collaboration. Instead, the politics of agitation of the narrow-minded Hindus gave way to Muslim nationalism to flourish which was capitalized by the Muslim leaders who later obtained a separate homeland for the security of their identities. The pivotal role of none of the Muslim leaders can be denied in this struggle. But, Muhammad Iqbal-a poet cum politician has carved out his name in the political history of the Sub-Continent in an innovative manner. The famous Allahabad Address of 1930 is the reflection of his political wisdom in which he seems to demand a separate state for the Muslims. This research article has attempted to explore how the Allahabad Address proved a milestone in Muslim political history. It has explained that the particular address provided a pace to the Muslim struggle for independence from the British as well as the Hindus. The directionless factions of the Muslim League (ML) were reintegrated to break the shackles. Barely three years later, they suggested the name “Pakistan” for a state purposed by Iqbal in 1930 and in 1940 Iqbal’s idea of a separate Muslim state was publically endorsed by Muhammad Ali Jinnah and other Muslim leaders. Sticking with this idea, within no time, the Muslims materialized the dream of Iqbal until August 1947. Keywords: Sub-Continent, Allama Iqbal, Allahabad Address, Muslims, State, and Impact.